How the computational methods can contribute to better knowledge of the ear - Gentil, Fernanda (2019)
The biomechanical behavior of the human ear can be studied using mathematical approaches, such as the finite element method. This methodology allows to perform simulations to evaluate the influence of sound transmission through all way of the ear, since the sound is selected by the outer ear to the inner ear. The finite element method is currently the preferred method for the numerical solution of partial differential equations, and it is used in several fields of the biological sciences. Due to its large applicability and efficiency, there are several works where this methodology is applied in different specialties, to analyze loads, strains or displacements, as in the case of the biomechanical study of the ear. From CT images, three-dimensional accurate computational models are created. The technique employs a set of calculations of numerical analysis for solutions of kinematic (displacements and rotations) and mechanical aspects (strength, stress, pressure, deformation). The use of these computer models enables the motion analysis of all ossicular chain points at any moment.